Advantages of "National Curriculum". - Kholikova Khurshida Shukrillaevna (Zien Journals, 2022)
In this article, the advantages of the national curriculum, the rapid development of science and technology, the processes related to the transition to the digital economy are causing new socio-economic, political and cultural changes, and the importance of textbooks in the education of young people, who are considered to be the builders of the country's future, is incomparable. the word goes
Keywords: national curriculum; students; teachers; quarantine